A qualitative case study identifying leadership roles that significantly impact the integration of technology in secondary schools - Kipp, Charles Andrew (Kansas State University, 2019)
This case study explored leadership behaviors that are perceived to have significant impact in the integration of technology at the secondary level in a Southwest Kansas school district. The study focused on the identification of leadership methods in the supervision, management, and evaluation of effectively integrating educational technology into the classroom. The focus-group sessions were conducted with several secondary-level principals in order to determine issues concerning technology such as (a) vision, (b) curriculum and instructional practice, (c) professional learning communities, and (d) social advocacy/digital citizenship. Furthermore, focus-group sessions were conducted with principals in order to determine (a) pre-existing policy and practice concerning technology integration, (b) significance of leadership behaviors and technology integration in the school and classrooms, (c) difficulties with implementation of additional supervisory criteria concerning technology, and (d) recommendations of the principals in terms of technology supervision and evaluation. The study included two focus groups (one high school group and one middle school group) from one Kansas school district. The study involves multiple focus group interviews, field notes, and a review of documents and artifacts. The data analysis identified significant themes that illustrated existing and desired behaviors and practices that the participants perceived to have a significant impact on technology integration at the secondary school level.
Keywords: Qualitative; Technology; Education; Leadership; Secondary